2020
DOI: 10.3389/fneur.2020.00345
|View full text |Cite
|
Sign up to set email alerts
|

Injury Causes and Severity in Pediatric Traumatic Brain Injury Patients Admitted to the Ward or Intensive Care Unit: A Collaborative European Neurotrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI) Study

Abstract: Background: Traumatic brain injury (TBI) is the leading cause of death and disability in children. It includes a range of different pathologies that differ considerably from adult TBI. Analyzing and understanding injury patterns of pediatric TBI is essential to establishing new preventive efforts as well as to improve clinical management. Conclusion: Our study displays the most common injury causes and characteristics of pediatric TBI patients that are treated in the regular ward or ICU in Europe. Road-traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
(54 reference statements)
2
15
0
1
Order By: Relevance
“…This approximately corroborates with a study in UK major trauma center with 9.0% reported case fatality [ 5 ]. The estimated case fatality rate is higher than those reported in Europe [ 33 ], India [ 34 ], Australia [ 35 ] and United States [ 36 ], which reported 3.0%, 3.0% 0.87% and 4.5% respectively. However, our estimate is lower than the 22.8% reported in the US trauma registry [ 37 ].…”
Section: Discussionmentioning
confidence: 59%
“…This approximately corroborates with a study in UK major trauma center with 9.0% reported case fatality [ 5 ]. The estimated case fatality rate is higher than those reported in Europe [ 33 ], India [ 34 ], Australia [ 35 ] and United States [ 36 ], which reported 3.0%, 3.0% 0.87% and 4.5% respectively. However, our estimate is lower than the 22.8% reported in the US trauma registry [ 37 ].…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, in London, only 1% of moderate and severe paediatric TBI was found in cyclists who were hit by a car or fell of the bicycle, as opposed to the 39% of patients who were hit by a car as a pedestrian (2). Another European childhood TBI study found that only 25% of RTA victims were cyclists (9). These outcomes suggest there are several possibilities for prevention of moderate and severe TBI.…”
Section: Discussionmentioning
confidence: 96%
“…The last Dutch epidemiological study describes the incidence over 10 years ago (4). In keeping with adult studies, most paediatric studies reveal falls and RTAs as the most frequent mechanism of injury (9). However, children are passengers rather than drivers when it comes to motor vehicles and are more often involved as a pedestrian (9).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This practice creates a significant burden on pediatric IC units; about half of children with mTBI, admitted to an ICU have GCS 15. 54 There are five predictor variables to identify children requiring ICU-level care: GCS <15, non-isolated head injury, and on CT a midline shift >5 mm, absent cisterns, or intraventricular hemorrhage. 47,55 Implementing these predictors leads to ICU-admission rates of 66 to 81% in this group.…”
Section: Neurosurgical Interventionmentioning
confidence: 99%